Investigation of Resilience of Eccentrically Braced Frames Equipped with Shape Memory Alloys - Pirmoghan, Hamid; Khoshravi, Hossein; Sadeghi, Abbasali; Pouraminian, Majid; Noroozinejad, Farsangi Ehsan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Nowadays, the use of smart materials in structures is a major concern to structural engineers. The act of benefiting from numerous advantages of these materials is the main objective of researches and studies focused on seismic and structural engineering. In the present study, in addition to the development of finite element models of several steel frames using ABAQUS software, the effect of shape memory alloys (SMAs) on superelastic behavior and the various types of eccentric braces will be checked.
Keywords: shape memory alloy (SMA); super-elastic behaviour; response modification factor; shape memory effect; reduction factor; seismic resilience; stop z pamięcią kształtu; współczynnik modyfikacji; współczynnik redukcji; odporność sejsmiczna